MARLENA SIAGA (MASYARAKAT PEDULI PADEMI CORONA) - Luluk Fauziyah Januarti; Achmad Masfi (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
The low level of public awareness in breaking the chain of the spread of Covid-19 in Jeddung Village is of particular concern in community service programs. Based on the problem analysis, the community service program focuses on the following: 1) Little Marlena agent of change training, 2) Marlena Cadre Workshop, 3) village mini-workshop and formation of healthy compok, and 4) the practice of hand washing movements, and the use of good and correct masks via audio visual. There are three methods used, namely the educational method, the socialization method, and program evaluation. Data collection techniques in this service using interview techniques, questionnaires, and documentation. The impact of this service program shows that, forming agents of change from school-age children to increase public awareness of Covid-19 prevention will run optimally if a direct approach to the community is carried out by the local government and the village government. The results of a survey evaluation regarding public awareness of the prevention of Covid-19 in Jeddung Village showed a poor response to the aspects of frequent hand washing and using a hand sanitizer. However, the people of Jeddung Village have realized to wear masks if they want to travel, it's just that when their sick conditions are less aware of wearing masks.